A Study of the Efficacy of Various Nutrient Sources on the Growth and Yield of Cabbage - Maghfoer, Moch. Dawam; Koesriharti, Koesriharti; Islami, Titiek; Kanwal, N. D. S. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Research evaluated various nitrogen sources, and a supplementary foliar fertilizer or biochar on cabbage. It was conducted from July to October 2014 in Poncokusumo, Malang ca. 600 meters above sea level. The experiment used a randomized block design with four replications. The treatments were fertilized with different concentrations of urea, goat manure and selected substances i.e. 100% N urea (controls); 75% N urea + 25% N goat manure; 50% N urea + 50% N goat manure; 75% N urea + 25% N goat manure + foliar fertilizer (6-30-30), 50% N urea + 50% N goat manure + foliar fertilizer (6-30-30); 75% N urea + 25% N manure + biochar; and 50% N urea + 50% N goat manure + biochar. The dose of N fertilizer used was 69 kg ha-1. The results showed that a higher yield was recorded in the application of 75% N urea + 25% N goat manure and 50% N urea + 50% N manure with an addition of foliar fertilizer that was not significant with the application of 75% N urea + 25% N goat manure with the addition of biochar, resulting in a marketable yield of 68.84, 66.5 and 64.75 t ha-1, respectively.